FAKTOR FUNDAMENTAL DAN MAKRO EKONOMI YANG MENENTUKAN HARGA SAHAM PERUSAHAAN MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA - Hendro Sasongko (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2020)
The research intends to determine the stock price from fundamental (Current Ratio [CR], Return on Assets [ROA], Earning Per Share [EPS], Debt to Equity Ratio [DER]) and macroeconomic factors (Inflation Rate) of food and beverage companies on the Indonesia Stock Exchange. This type of research is a verification study with an explanatory survey method. The type of data used is secondary data with a sampling method that is purposive sampling. There are thirteen sample companies that use panel data regression analysis methods, with regression models that meet the classical assumption test. Based on the results of the study note that simultaneously CR, ROA, EPS, DER, and Inflation variables determine the stock price. Partially, CR does not determine the stock price, ROA partially determines the stock price positively and significantly. EPS partially determines stock prices positively and significantly. DER partially does not determine stock prices. The inflation rate partially determines stock prices negatively. The implication of this research is that companies really need to pay attention to the level of profitability because the ratio is very influential on investor perceptions. In addition, macroeconomics must also be considered because it affects the perception of investors in the company's position.